A Neurociência e o Ensino-Aprendizagem em Ciências: um diálogo necessário - Rezende, Mara Regina Kossoski Felix (2008)
This study a necessary dialogue between the Neurociência and the process has as focus teach-learning, but especificadamente the study of the brain, involving Ensino de Ciências of the eighth year of Basic Ensino, while possibility of dialogues and development of reflexiva one practical capable to contextualizar the cerebral contents. It was opted to a descriptive research of exploratório matrix, essentially, qualitative. For the attainment of the data interviews, questionnaires and applicability of a kit had been become fullfilled that composes the neuropedagógica box. The sample consisted of fifteen professors of particular and state schools that submitted to the resources offered in the neuropedagógico kit, potencializaram the capacity see-to learnreaprender and the possibility of the construction of the knowledge regarding the brain with differentiated resources. To these questionings, it was looked to reflect on the activity of the professors ahead of the process to teach to teach, to learn to teach, according to perspective of the Neurociência, in leading the new fields of studies and of the pedagogical knowledge. It was standed out that this passage of research of practical theory and determined throughout this dissertação reflection, matureness of ideas, complicity with the application of the instruments that composes the neuropedagógico kit and comprometimento in the action. Of this form, one concludes that the practical construction of one pedagogical one structuralized from dialogues between the Neurociência is possible and Ensino de Ciências, since the worked subjects had led to the reality of the daily one of the students in classroom For such, had crossed the thoughts of Almeida (1997), Valle and Capovilla (2004); Lent (2002); Zimmer (2004), Barbosa (2005, 2007); Olivier (2006); Restak (2006); Relvas (2005); Morin (2005); Steiner (1992,2000), Vygotsky (2001,2003), Ausubel (2003) and Wallon apud Caixeta (2007) that they had lead in them, in the evolution of its studies, to a more pleasant form of if understanding the cerebral process. Key-words: Learning. Education of Sciences. Neuroscience. Area of concentration: Formation of professors.